One year after - Forstchen, William R. (New York, NY Tom Doherty Associates, LLC, 2016)
"After months of suffering starvation, war, and countless deaths, the survivors of Black Mountain, North Carolina, are beginning to recover technology and supplies they had once taken for granted. When a 'federal administrator' arrives in a nearby city, they dare to hope that a new national government is finally emerging. Progress is halted when the young men and women in the community are drafted into the 'Army of National Recovery.' Town administrator John Matherson and the people of Black Mountain protest vehemently. But 'the New Regime' is already tyrannizing one nearby community, and it seems that Matherson's friends and neighbors will be next."--Page 4 of cover.
Sequel to: One second after.
105552
Keywords: Regression (Civilization) -- Fiction; Nuclear warfare -- Fiction; Survivalism -- Fiction; Apocalyptic fiction; Science fiction